Synergistic criteria and indicators for evaluating Small Enterprise Performance - Erkin Shavqiyev; D. H. Davirova (Goodwood Publishing, 2025)
Purpose: This study investigates the criteria and indicators essential for determining the efficiency of small industrial enterprises, a sector crucial for sustainable economic development yet often underserved by traditional evaluation frameworks. Research methodology: The research draws on existing synergistic efficiency frameworks, particularly those developed by Kondratiev et al. (2022), and integrates insights from production capacity modeling to propose a refined system of indicators suitable for small enterprises. Utilizing a mixed-method approach combining economic-mathematical modeling, statistical analysis, and case study evaluation, the study examines fluctuations in equipment utilization, labor productivity, and material efficiency over a thirty-year period. Results: Results indicate that while material efficiency remains relatively stable, labor and equipment productivity are highly variable, reflecting inconsistencies in workforce management and capital utilization. These findings underscore the limitations of conventional metrics and the need for multidimensional models that incorporate internal and external performance drivers. Contribution: This research contributes to the academic discourse by filling a gap in performance evaluation literature for small-scale industry and offers a foundation for future work in developing sector-specific benchmarking systems, performance dashboards, and policy instruments to support sustainable industrial growth. Implication: The implications are significant: small enterprises require adaptive, real-time efficiency monitoring tools that are both theoretically sound and practically implementable.